Waste Electrical and Electronic Equipment Recycling : Aqueous Recovery Methods - Veglio, Francesco; Birloaga, Ionela (Woodhead Publishing series in electronic and optical materials., 2018)
Water Electrical and Electronic Equipment Recycling: Aqueous Recovery Methods provides data regarding the implementation of aqueous methods of processing of WEEEs at the industrial level. Chapters explore points-of-view of worldwide researchers and research project managers with respect to new research developments and how to improve processing technologies. The text is divided into two parts, with the first section addressing the new research regarding the hydrometallurgical procedures adopted from minerals processing technologies. Other sections cover green chemistry, bio-metallurgy applications for WEEE treatment and the current developed aqueous methods at industrial scale. A conclusion summarizes existing research with suggestions for future actions.